The Relations between Labour Market Institutions and Employment of Migrants - Domicián Máté; İmran Sarihasan; Krisztina Dajnoki (Amfiteatru Economic Journal, 2017)
International migration is one the greatest challenges in the era of globalization and has become a focus of political debate in recent years. Although the economic effects of migration increase the efficiency of labour markets, some governments have rigorously rejected solutions proposed for the current refugee crisis. Meanwhile, immigration policies have recently become stricter in several OECD countries. Based on this conceptual framework, several labour market institutions, such as a minimum wage, unemployment benefits, union density, and active labour market policies etc., are analysed in the context of enhancing the employment of immigrants. In order to support the findings of literature this paper concentrates on the determinants of immigration tendencies and dynamic regression models analysed to clarify how these institutions can affect native- and foreign-born migrants. Hence, our results also highlight that various reforms need to enhance the efficiency of labour market migration policies.
Keywords: K37; J21; J15; 330; panel analysis; migrant policies; labour institutions; employment growth